Shift dynamics near non-elementary T-points with real eigenvalues - knobloch,J; Lamb,JSW; webster,KN (Journal of Difference Equations and Applications, 2017)
We consider non-elementary T-points in reversible systems in R2n+1. We assume that the leading eigenvalues are real. We prove the existence of shift dynamics in the unfolding of this T-point. Furthermore, we study local bifurcations of symmetric periodic orbits occurring in the process of dissolution of the chaotic dynamics.